The effect of phosphoric acid etching duration on the bond strength of universal adhesive on enamel with or without erosion - Huang, Shasha; Chai, Yuan; Niu, Guangliang (Frontiers in Dental Medicine, 2025)
This study evaluated the effect of phosphoric acid etching duration on the bond strength of a universal adhesive (UA) on enamel, both with and without erosion (0.3% citric acid with a pH of 2.6 for 5 min four times a day for five consecutive days). Flat, polished bovine incisors (n = 60) were divided into two groups according to different enamel conditions, and were further divided into three subgroups (n = 10) according to phosphoric acid etching duration: 0 [self-etch (SE) mode], 3, and 15 s [etch-and-rinse (ER) mode]. A shear bond strength (SBS) test was performed after applying the UA and composite blocks. Surface topography and roughness were assessed after the phosphoric acid treatment of the incisors, with or without erosion, using scanning electron microscopy and a profilometer, respectively. In the normal enamel group, the SBS values were significantly higher in the ER mode group, while neither the phosphoric acid etching duration nor the etching mode affected the SBS or roughness in the eroded enamel group. In summary, applying UA after phosphoric acid etching using the SE mode may be sufficient for eroded enamel, while reducing the phosphoric acid etching duration to 3 s may be acceptable in resin restoration with normal enamel.